2012
DOI: 10.1007/s00707-012-0652-x
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-electro-mechanical response of 1–3–2 piezoelectric composites: effect of fiber orientations

Abstract: A micromechanics-based analytical model is developed to evaluate the performance of 1-3-2 piezoelectric composite where both matrix and fiber materials are piezoelectrically active. A parametric study is conducted to investigate the effects of variations in the poling characteristics of the fiber phase on the overall thermo-electro-mechanical behavior of a 1-3-2 piezocomposite. The performance of the 1-3-2 composite as a transducer for underwater and biomedical imaging applications is analyzed. The proposed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The MFC is a popular material for extension mode piezoelectric actuation of flexible structures. Besides these well-known PFCs, many other extension mode PFCs have also been proposed in the literature [512], and, in this concern, some recent studies [1318] dealing with the coupled electromechanical phenomenon in piezoelectric/flexoelectric materials may be useful for further development of PFC or piezoelectric actuators. However, the available studies on the PFCs indicate a great deal of research on the development of extension mode PFCs whereas a few studies on the development of shear mode PFCs have been observed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The MFC is a popular material for extension mode piezoelectric actuation of flexible structures. Besides these well-known PFCs, many other extension mode PFCs have also been proposed in the literature [512], and, in this concern, some recent studies [1318] dealing with the coupled electromechanical phenomenon in piezoelectric/flexoelectric materials may be useful for further development of PFC or piezoelectric actuators. However, the available studies on the PFCs indicate a great deal of research on the development of extension mode PFCs whereas a few studies on the development of shear mode PFCs have been observed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a novel 1-3-2 piezoelectric composite is proposed to overcome the instability of 1-3 composite structure and at the same time inherits the advantages of 1-3 composite [6][7][8][9][10][11][12][13][14]. 1-3-2 piezoelectric composite consists of two layers which are mechanically connected in series.…”
Section: Introductionmentioning
confidence: 99%
“…They also manufactured 1-3-2 composite samples to measure the parameters, such as hydrostatic pressure stability, temperature stability, voltage response and receiving voltage sensitivity. Sakthivel and Arockiarajan [10,11] have developed a micromechanics-based analytical model to capture the effective thermo-electro-mechanical response of 1-3-2 composite and predicted the electro-elastic constants. Zhou et al [12] have fabricated 1-3-2 type multi-element piezoelectric composite samples and measured their properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalamkarov and Savi (2012) proposed a smart grid–reinforced composite that is composed of a large number of periodically arranged cylindrical reinforcements and piezoelectric actuators. Sakthivel and Arockiarajan (2012) addressed a model of 1-3-2 PZC for the material of transducer in underwater and biomedical imaging applications. Panda and Panda (2015) and Panda et al (2015) used transversely/longitudinally poled short piezoelectric fibers for improved flexibility of earlier PZCs such as PFRC (Mallik and Ray, 2003) and AFC (Bent, 1997).…”
Section: Introductionmentioning
confidence: 99%